1998
DOI: 10.1103/physrevlett.81.1215
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Raman Self-Conversion of fs-Pulse Frequency due to Impulsive Excitation of Molecular Vibrations

Abstract: We report on the observation of a Raman frequency conversion mechanism different from the usual Stokes (anti-Stokes) stimulated process. A continuous down-shift of laser pulse frequency was measured for sufficiently short ͑#40 fs͒ pulses propagating in gaseous SF 6 . We attribute this behavior to the extremely nonstationary nuclear response of SF 6 molecules to the light field with a duration shorter than the period of the Raman-active vibration. [S0031-9007(98)06773-8] The purpose of this Letter is to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 10 publications
4
35
0
Order By: Relevance
“…When the pulse duration of the pump pulse is shorter than a molecular motional period, the dynamics changes to impulsive stimulated Raman scattering that continuously shifts the frequency of the short pump pulse to a lower frequency. This was observed in previous researches [13,14,19] and in the present research as shown in Figure 4. This process does not require any phase matching.…”
Section: Excitation Of Rotational Wavepackets By the Pump Pulse And Tsupporting
confidence: 90%
See 4 more Smart Citations
“…When the pulse duration of the pump pulse is shorter than a molecular motional period, the dynamics changes to impulsive stimulated Raman scattering that continuously shifts the frequency of the short pump pulse to a lower frequency. This was observed in previous researches [13,14,19] and in the present research as shown in Figure 4. This process does not require any phase matching.…”
Section: Excitation Of Rotational Wavepackets By the Pump Pulse And Tsupporting
confidence: 90%
“…Such coherent motion induces the ultrafast variation of the refractive index of the medium, modulating the frequency of a laser pulse with an arbitrary wavelength copropagating with the pump pulse [13] as well as that of the pump pulse [13][14][15][16]. The coherent molecular motion is also expected to have effects on the amplification characteristics of the FWOPA.…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations